Pande Besi Ethics in Transactions and Heirloom Production Rituals - Siti Mardiyah; Robiatul Auliyah (Karsa: Journal of Social and Islamic Culture, 2020)
This study seeks to reveal the application of business ethics in the traditional Marsyudi blacksmith business in Paterongan Village. This study uses qualitative methods with a case study approach. The informants in this study were four, namely one main informant as the blacksmith owner and three supporting informants who were employees and customers. This research site is carried out at the Marsyudi traditional blacksmith business site, namely in Tok Koneng Hamlet, Paterongan Village, Galis District, Bangkalan Regency. The results of this study indicate that the application of business ethics to traditional Marsyudi blacksmith business is good. First, Marsyudi's traditional blacksmith business implements a belief value in the implementation of the down payment payment system, the value of giving equal prices in the heirloom selling price and the value of freedom of choice in credit payment transactions made by buyers. Second, the application of ritual ethics before carrying out heirloom production. Rituals in heirloom production that are applied to his efforts are jhejeh rituals, rituals for distributing porridge or sticky rice, reading basmalah and bathing keris heirloom by using flower water. All of these rituals are intended for the craftsman to be safe and produce good quality heirloom products. These findings are in line with the theory of teleology because the purpose of business ethics carried out by the traditional Marsyudi blacksmith business is for the good, not for evil.